2010
DOI: 10.3109/15376511003793325
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid-induced apoptosis in HepG2 cells: Generation of oxidative stress and Bcl-2 down-regulation

Abstract: Isoniazid (INH) is a first-line antibiotic used in the treatment of infections caused by Mycobacterium tuberculosis. However it has a serious limitation of being hepatotoxic. Delineating the mechanism underlying INH-induced hepatotoxicity may be beneficial in devising ways to counteract its toxic manifestations. Studies in human hepatoma HepG2 cells have indicated that INH exposure causes induction of apoptosis. This study was aimed at identifying the key components/pathways of the INH-induced apoptotic pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…soniazid (INH), since its introduction in the year 1952, still serves as a frontline drug in tuberculosis treatment (1). Despite the fact that INH has been widely used as a first-line antitubercular agent (2,3), its therapeutic value is usually accompanied by severe hepatotoxicity and lethal hepatic injury (4,5).…”
mentioning
confidence: 99%
“…soniazid (INH), since its introduction in the year 1952, still serves as a frontline drug in tuberculosis treatment (1). Despite the fact that INH has been widely used as a first-line antitubercular agent (2,3), its therapeutic value is usually accompanied by severe hepatotoxicity and lethal hepatic injury (4,5).…”
mentioning
confidence: 99%
“…The decreased activities of SOD and CAT observed in INH treated mice was probably due to the interaction of the accumulated free radicals with the associated metal ions or with the active amino acids of these enzymes. During hepatotoxicity these enzymes are structurally and functionally impaired by free radical resulting in liver damage [14]. Our results showed that after administration of INH in combination with SH11 the levels of MDA (Figure 6) were decreased and the activities of the antioxidant enzymes SOD (Figure 7) and CAT (Figure 8) were amended.…”
Section: Discussionmentioning
confidence: 57%
“…The concept that RMP-INH mediated apoptotic cell death of hepatocytes is mediated via mitochondrial cytochrome c release and mitochondrial mediated caspase activation is supported by a number of studies, which show that RMP-INH mediated mitochondrial ROS production inhibits Nrf2 function [140] and induces pro-caspase-8 & 10 activation in rats [126, 140]. Furthermore, altered mitochondria-mediated changes in Bcl-2/Bax content, mitochondrial release of cytochrome c and caspase activation were also all shown to be responsible for INH- induced mitochondria mediated apoptosis in HepG2 cells [132]. Detection of cytochrome c protein in the cytosol of mouse hepatocytes treated with RMP-INH also revealed its leakage from mitochondria [128].…”
Section: Rifampin and Isoniazid Hepatotoxicitymentioning
confidence: 96%
“…In HepG2 cells, INH metabolites also cause manganese superoxide dismutase [127, 131], catalase, and glucose-6-phosphate dehydrogenase modifications [132]. These altered antioxidant functions lead to the loss of hepatocyte ability to efficiently detoxify acetylhydrazine and hydrazine.…”
Section: Rifampin and Isoniazid Hepatotoxicitymentioning
confidence: 99%
See 1 more Smart Citation